Linda Goodman's Love signs : a new approach to the human heart. - Goodman, Linda, 1925-1995 (Harper Perennial, 2014)
A guide to astrological compatibility advises men and women on their chances for success and happiness in their dealings and relationships with individuals born under each sign of the zodiac.